Mental health experiences and coping strategies of BAME care workers who worked in nursing and residential care homes during the COVID-19 pandemic in Luton, England - Isabella Kabasinguzi; Nasreen Ali; Peter Ochepo (BMC, 2023)
Abstract Background The COVID-19 pandemic intensified the risk factors for poor mental health among care workers in the UK. However, there is inadequate evidence on the mental health impact of COVID-19 on Black, Asian, and minority ethnic (BAME) care workers in particular. This study seeks to explore mental health experiences and coping strategies of BAME care workers who worked in nursing and residential care homes during the COVID-19 pandemic. Method This is a qualitative study conducted between February and May, 2021 in Luton, England. A sample of n = 15 care workers from BAME background working in nursing and residential care homes were recruited purposively using the snowball sampling technique. In-depth interviews were conducted around topics such as views on COVID-19, the impact of the COVID-19 pandemic on mental health and coping during the COVID-19 pandemic. Data from the interviews was analysed using the Framework Analysis Approach. Results The COVID-19 pandemic had a negative impact on the participants' mental health as they experienced stress, depression, anxiety, trauma and paranoia. The majority of the participants explained that they managed their mental health by belief in God and religious practices, by keeping themselves busy doing activities they were passionate about, following government guidelines on the prevention of COVID-19, seeing the service users happy and some participants managed through support that was offered by the government. However, some participants did not have any support for their mental health. Conclusion Issues such as increased workload associated with COVID-19 restrictions engendered mental health problems among BAME care workers, however, the workload only further increased during the pandemic, but the health and social care sector was already affected by heavy workload due to staff shortages and this needs to be addressed through increasing their wages to encourage more people to work in the health and social care sector. In addition, some BAME care workers never received any support for their mental health during the pandemic. Hence, integrating mental health services such as counselling, supportive psychotherapy and recreational therapies in care homes could help to support the mental health of care workers in the COVID-19 era.